Individual, family and social-related factors of eating behavior among Chinese children with overweight or obesity from the perspective of family system - Zhu, Hanfei; Zhao, Kang; Huang, Lidong; Shi, Wenbing; Tang, Chulei; Xu, Ting; Zhu, Shuqin; Xu, Qin; Li, Xiaonan; Chen, Yinhua; Liu, Qianqi; Yang, Linhui (Frontiers in Pediatrics, 2024)
Purpose The purpose of the present study is to examine the factors contributing to the development of eating behavior in overweight and obese children from the perspective of the family system. Methods A cross-sectional survey was conducted by using convenience sampling method to select 388 participants in two primary schools in Jiangsu, China. Individual, family and social-related factors were collected. Individual factors included age, gender, ethnicity, single child, social anxiety, depression, physical activity, sleep duration, screen time. Family factors included family environment, family structure, family function, family income, parenting style, parental feeding behavior, home food environment and marital satisfaction. Social-related factors included place of residence, number of surrounding restaurants and social support. Univariate analysis, correlation analysis and multivariate analysis were used to identify factors of eating behavior among Chinese children with overweight and obese. Results In this study, 388 participants took part with a 94.865% response rate. In the univariate analysis, the significant differences regarding Dutch Eating Behavior Questionnaire (DEBQ) scores were found between children aged 6–9 years and those aged >9 years. Correlation analysis indicated that parent's nutrition literacy (r = 0.118, P < 0.05), pressure to eat (r = 0.212, P < 0.01), perception of child weight (r = −0.112, P < 0.05) and family function (r = −0.563, P < 0.01) were associated with children's eating behavior. With regard to psychosocial factors, children's social anxiety (r = 0.299, P < 0.01) and depressive symptoms (r = 0.081, P < 0.05) were in positive correlation with eating behavior. The independent variables included in the initial model were age, father's employment status, social anxiety, maternal punishment and harshness, parents' nutrition literacy, pressure to eat, family function and perception of child weight. These variables in the final model accounted for 20.7% of the variance. Conclusion We found that age, father's employment status, social anxiety, maternal punishment and harshness, parents' nutrition literacy, pressure to eat, family function and perception of child weight have great effect on children's eating behavior who are overweight or obese. As early childhood is a critical timeline for child development, children's social anxiety, parenting style, parent's nutrition literacy, parent's feeding behavior and family function should be intervened to promote eating behavior. Intervention programs aimed at promoting healthy eating behaviors among children, thereby mitigating the risk of pediatric obesity, should primarily target parents.